Diagnosis of Rhinocerebral Mucormycosis by Treatment of Cavernous Right Internal Carotid Artery Occlusion With Mechanical Thrombectomy: Special Case Presentation and Literature Review - Kashyap, Samir; Bernstein, Jacob; Ghanchi, Hammad; Bowen, Ira; Cortez, Vladimir (Frontiers in Neurology, 2019)
Background Mucormycosis is a rapidly progressive, angioinvasive fungal infection that has a predilection for the paranasal sinuses and adjacent mucosa. Rhinocerebral mucormycosis (RCM) is the most common form and is known to invade the skull base and its associated blood vessels – leading to mycotic aneurysms, ischemic infarcts, and intracerebral hemorrhage. There are documented cases of mechanical thrombectomy in ischemic stroke due to RCM, however, there no known cases that were diagnosed primarily by histological and pathological analysis of the embolus. We present a case of treatment of large vessel occlusion that led to the diagnosis and treatment of RCM. In addition, we demonstrate a case of successful maintenance therapy using a new antifungal agent, posaconazole. Case Presentation A 21 year-old male inmate with history of type 1 diabetes presented with generalized weakness, abdominal pain, and right eye blindness and ophthalmoplegia after assault in prison. He underwent treatment for diabetic ketoacidosis, but subsequently developed left hemiplegia was found to have complete occlusion of his right internal carotid artery. He underwent successful mechanical thrombectomy and pathological analysis of the embolus revealed a diagnosis of mucormycosis. He completed a course of amphotericin B, micafungin, and posaconazole. With the aid of acute rehabilitation he achieved a modified Rankin score of 2. Discussion We review the pathogenesis, diagnosis and treatment of RCM. A comprehensive multidisciplinary is critical to successful management of this often-fatal disease. Early diagnosis and treatment are essential in RCM as delaying treatment by more than 6 days significantly increases mortality. Treatment includes surgical debridement and intravenous antifungal therapy (amphotericin B + micafungin or caspofungin) for a minimum of 6-8 weeks. Newer antifungals such as isavuconazole and posaconazole are showing equivalent efficacy in the treatment of this disease and are emerging as potential new first-line agents.